Hubungan antara Kemahiran Sosial dan Pembelajaran Secara Kolaboratif dalam Talian di Kalangan Pelajar UTHM - Nur Sabrina Zainal,; Siti Aisyah Salim, (Research in Management of Technology and Business, 2024)
Online learning has evolved into a transformative approach, offering benefits such as enhanced accessibility and a flexible learning experience. Educational institutions welcome this innovative method for teaching and learning (PdP) purposes. However, there are some issues that result from the lack of in-person engagement, which hinders the growth of interpersonal skills, and technological obstacles, which cause disparities, underline the limitations of the method, emerge as an urgent problem statement. The challenge lies in finding a harmonious balance between the advantages of online learning, such as enhanced accessibility and flexible learning experiences, and the critical need for face-to-face interaction that fosters interpersonal skills. Additionally, addressing technological barriers becomes essential to ensure a more equitable and inclusive educational landscape. Despite these obstacles, the adaptability of online learning is particularly evident in times of crisis, requiring a balanced perspective to fully exploit its potential for effective and inclusive education. Therefore, The purpose of this study is to determine the social skills and online collaborative learning usage levels of UTHM students, as well as to investigate the correlation between these factors. Using online surveys and questionnaires, Universiti Tun Hussein Onn Malaysia (UTHM) obtained data from 203 respondents for quantitative study. Using the Statistical Package for Social Science (SPSS), the quantitative data will be analysed and the results will be presented as frequency, percentage, mean, and standard deviation. Notably, there is a substantial link between all the factors with social skills, with the highest correlation coefficient observed in the interaction aspect, reaching 0.904.